The investigation of Solar Radio Burst Type III accompanied by type II associated with solar activities due to magnetic reconnection / Nurulhazwani Husien - Husien, Nurulhazwani (2019)
Solar Radio Bursts Type II (SRBT II) commonly occurs after the formation of Solar Radio Bursts Type III (SRBT III) in association with the solar flares and Coronal Mass Ejections (CMEs) events due to magnetic reconnection process. In the previous study, the SRBT II, SRBT Type III and their correlation with solar flares and CMEs respectively have not been discussed in details. The objective of this research is to study the correlation for SRBT II and SRBT III related to solar flares and CMEs events due to magnetic reconnection theory. The importance of these correlations are to enhance the understanding of the particles behaviour during the events over these two types of solar radio burst which are related to explosive phenomena such as solar flares and CMEs. The data for both SRBT III and SRBT II can be obtained from the e -CALLISTO website. Meanwhile, the data for solar flares and CMEs were obtained from the Solar Monitor website and Computer Aided CMEs Tracking website respectively. There are 44 data have been collected starting from 2012 until 2017. The Pearson Correlation Coefficient is a method used in obtaining the correlation of the variables of SRBT III and SRBT II, solar flares and CMEs events